Experimental investigation of tensile and bond properties of Carbon-FRCM composites for strengthening masonry elements. (1st November 2017) - Carozzi, Francesca Giulia; Bellini, Alessandro; D'Antino, Tommaso; de Felice, Gianmarco; Focacci, Francesco; Hojdys, Łukasz; Laghi, Luca; Lanoye, Emma; Micelli, Francesco; Panizza, Matteo; Poggi, Carlo
Abstract: Fabric Reinforced Cementitious Matrix (FRCM) materials are composed of a dry fiber grid embedded in an inorganic matrix, which may contain short fibers. These materials are particularly well-suited for the reinforcement of masonry structures due to their high compatibility with the substrate, vapor permeability and durability against environmental agents. The most important information needed for the characterization of these composite systems, for use as strengthening materials of masonry structures, are the tensile behaviour and the shear bond properties. A Round-Robin Test was organized by the RILEM Technical Committee 250-CSM and the Italian association Assocompositi in order to experimentally characterize different FRCM systems composed of PBO, carbon, glass, basalt, aramid and steel textiles embedded in cementitious or lime-based mortars. The systems were tested at different universities and research centers in Europe in order to investigate the influence of samples preparation, test set-up and instrumentation. In this paper, the experimental tests performed on Carbon-FRCM systems are described and discussed. Important aspects are analyzed herein: differences in the testing procedure and instrumentation, influence of textile geometry and mechanical properties of the constituent materials, importance of specimen preparation and curing conditions. Moreover, a comparison between tensile and shear tests is reported in order to determine a reliable procedure towards the complete characterization of an FRCM material.